2020
DOI: 10.1097/ta.0000000000002936
|View full text |Cite
|
Sign up to set email alerts
|

The management of occult hemothorax in adults with thoracic trauma: A systematic review and meta-analysis

Abstract: BACKGROUND Hemothorax is a common sequelae following thoracic trauma and is associated with significant morbidity and mortality. Current guidelines recommend all traumatic hemothoraces be considered for drainage with tube thoracostomy (TT), regardless of size. With increasing use of computed tomography, smaller hemothoraces not seen on x-ray (defined as an occult hemothorax) are frequently detected. METHODS This systematic review was performed to gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
3
0
5
Order By: Relevance
“…This is in contrast to another study that identified displaced rib fractures and moderate-sized pneumothorax as significant factors associated with chest tube placement in patients with blunt chest trauma and occult pneumothorax [ 28 ]. In another study, the conservative treatment of occult hemothorax failed in about 23% of patients, in which hemothorax volumes of more than 300 mL and the need for mechanical ventilation had the highest predictive value for chest tube placement [ 29 ]. However, a conservative approach to occult pneumothorax detected only on CT can be a safe procedure, even for mechanically ventilated patients [ 11 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to another study that identified displaced rib fractures and moderate-sized pneumothorax as significant factors associated with chest tube placement in patients with blunt chest trauma and occult pneumothorax [ 28 ]. In another study, the conservative treatment of occult hemothorax failed in about 23% of patients, in which hemothorax volumes of more than 300 mL and the need for mechanical ventilation had the highest predictive value for chest tube placement [ 29 ]. However, a conservative approach to occult pneumothorax detected only on CT can be a safe procedure, even for mechanically ventilated patients [ 11 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Az úgy-nevezett spontán haemothorax jóval ritkább, ennek számos oka van: többek között malignus mellüregi folyamat, pleuralis összenövések elszakadása, tüdőembolia antikoaguláns kezelése, Ehlers-Danlos-szindróma, neurofibromatosis miatt spontán rupturált arteria (a.) intercostalis vagy a. mammaria, az a. pulmonalis malformációi (Rendu-Osler-Weber-szindróma), endometriosis, exostosis, thrombocytagátló kezelés kisiklásának következménye [1][2][3].…”
Section: Eredeti Közleményunclassified
“…Általános irányelvként, amennyiben a drénen ürülő vér mennyisége meghaladja az óránkénti 200 ml-t 3-4 órán keresztül a csövezést követően, vagy több mint 1500 ml vér ürül 24 óra alatt, és a keringés stabilitása transzfúzióra szorul, műtét javasolt [1][2][3][4][5][6][7][8][9][10][11]. A döntést azonban befolyásolják az aktuális körülmények, a beteg általános állapota, a BMI, a társbetegségek.…”
Section: Eredeti Közleményunclassified
See 2 more Smart Citations